The Utilization of the Reading Corner as a Learning Resource That Supports Literacy in Elementary School Students - Abdul Rokip (Journal of Educational Studies, 2025)
This research aims to describe the use of reading corners as a learning resource that supports the improvement of student literacy at SDN 3 Labuhan Haji. The background of this research departs from the importance of literacy culture in the elementary school environment as the foundation of critical, creative, and communicative thinking skills. The research method used is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research subjects include classroom teachers, school librarians, and students in grades IV and V. The results of the study show that the reading corner is optimally used as an additional learning tool outside of class hours, a media for enriching thematic reading, and a reading reflection room for students. The existence of a reading corner has been proven to increase reading interest, the ability to understand texts, and foster a reading attitude among students. However, the use of reading corners still faces obstacles such as limited book collections and lack of variety of literacy activities. Thus, support from schools and the community is needed to enrich reading resources and develop sustainable literacy programs.